Contrast Induced Nephropathy and its Predictors after Primary Percutaneous Intervention - Nasrullah, Aftab Ahmed Solangi, Amir Jamil, Zahirullah, Khalid, Rizwan Ahmed Yaqoob (Pakistan Journal of Medical & Health Sciences, 2022)
Background: contrast-induced nephropathy (CIN) is the most common complications associated with contrast media after angiographic procedures. The therapeutic intervention for CIN after the procedure, to date, is not yet conclusive. Therefore, the main reliance for the management of CIN is considered to be adequate assessment of risk-benefit and the preventive strategies. A little research has been done to identify the predictors of CIN in Pakistan. Objective: To assess the incidence and the predictors of CIN in our setting. Methodology: A total of 120 patients of Punjab Institute of Cardiology, Lahore who underwent primary PCI during January to July 2022, were observed to CIN through cross-sectional observational study. The baseline and some postprocedural laboratory findings, angiographic and interventional characteristics were observed on a pre-formed Performa and the data was analyzed using SPSS. Logistic regression analysis was implied to assess the independent predictors of CIN. Results and conclusion: CIN developed in 15% of the patients. LVEF, admission blood glucose, haemoglobin, eGFR, and contrast volume greater than 100 ml were all shown to be linked with CIN in univariate analysis. Age, eGFR, admission serum glucose, diabetes mellitus, and contrast volume more than 100 ml were shown to be independent predictors of CIN in the study participants.